Masyarakat Muslim Melayu di Singapura: Kajian Terhadap Isu dan Tantangan dalam Dakwah dan Pemikiran Islam Era Globalisasi - WZ Kamaruddin bin Wan Ali; Ahmad Zuhdi bin Ismail (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2017)
This paper aims to examine and assess the position of Islam as al-Din or religion for Malay Muslim community in Singapore. By using primary and secondary sources in the field of Islamic thought, the main and primary issues faced Malay Moslem society from various ranks, as well as internal, external and et cetera in addition to studying the methods and approaches applied by MUIS (Majelis Ugama Islam Singapore) specifically as the Islamic supreme and organization in the republic to solve the problems that arise in society since the first. The result of the study showed that Islam in Singapore is ASWJ (Ahlus Sunnah Wal Jamaah), as any other country in the overseas, but rather obvious distinction is due to the nature and attitude of openness and positiveness shown by Malay Muslim society in accepting diversity and different forms and thoughts. In summary, they are united in the difference “agree to disagree.”